Nilai-Nilai Pendidikan Agama Islam dalam Kitab Nasāʾihul ‘Ibād dan Relevansinya dengan Kurikulum Merdeka - Ilham Aunur Rhofiq; Mohamad Yahya Ashari; Agus Mahfudin (Jurnal Teologi Islam, 2025)
This study aims to examine the values of Islamic education in the book Nasāʾihul ‘Ibād and its relevance to the Islamic Religious Education (PAI) material in the Independent Curriculum for high school level. Islamic Religious Education plays a very important role in shaping the character of students, especially amidst the current moral crisis. The book Nasāʾihul ‘Ibād by Sheikh Nawawi al-Jawi contains the values of faith, sharia, and morals that are relevant to current educational challenges. The method used is a qualitative approach with a Systematic Literature Review approach. The results of the study indicate that the values in Nasāʾihul ‘Ibād include faith, obedience, five daily prayers in congregation, fasting, honesty, humility, social concern, avoiding reprehensible morals, and cultivating good morals. It is relevant to the dimensions of Islamic educational values in the independent curriculum, such as piety, noble character, and independence. This book has the potential to be used as an additional reference in Islamic Religious Education (PAI) learning oriented towards the formation of Islamic and moderate character. The relevance between the two is as follows: relevance in terms of aqidah values is that both share a similarity in emphasizing active and productive faith in social life. Relevance in terms of sharia values is that both are aligned in emphasizing that Islamic sharia teachings must shape the character and social responsibility of students. Meanwhile, relevance in terms of moral values is that both sources aim to shape individuals with noble character, able to live harmoniously in society, and possess a high social awareness, while avoiding bad morals.